The theory of behavior of gasfulled pores in crystalline and amorfhous bodys - Yu. V. Levinsky (Тонкие химические технологии)
It is shown that, in crystalline and amorphous solids, the closed pore always contains gas, the pressure of which should be taken into account when calculating the rate that the pore size varies. Sets of differential equations describing the kinetics of varying the pore size and gas pressure in pore are suggested for two mechanisms of behavior of closed in compact powders. The behavior of the pores is analyzed for the general case at comparable values of the surface tension forces, gas pressure, and external pressure, as well as for various particular cases. The features of behavior of the pores in an infinite space and in the solid of final sizes, with the slow and rapid diffusion of the gas in the solid, if the filled with one-atomic and two-atomic gasses, and of the ensemble of the pores are established. The causes are analyzed, and methods for calculating the swelling of the articles at the final stage of sintering are suggested.